The Effect of Marketing Mix on Purchasing Decisions at Pustaka Merah Hitam Bookstores in Makassar City - Al-Munahar Bin Harris; Herlina Sakawati; Aris Baharuddin (Public Resource Innovation Management and Excellence, 2026)
The emergence of various kinds of competition in the business world encouragesbusiness actors to carry out good marketing strategies to ensure the survival of acompany. Marketing strategy is very important in the continuity of marketing activitiesand especially in carrying out a business activity which is a means to achieve a goal inbusiness activities. This study examines the influence of the marketing mix (marketingmix) on purchasing decisions at the red and black library bookstore in Makassar City.The purpose of this study was to describe and determine the influence of the marketingmix on purchasing decisions at the red and black bookstores in Makassar City. Thisresearch approach is quantitative. This research was conducted at the red and blacklibrary bookstore in Makassar City from January to February 2023. The sample used was 96 people. Data collection techniques in the form of observation, questionnaires, anddocumentation. Data analysis techniques include validity test, reliability test, normalitytest, descriptive analysis, simple linear regression analysis, correlation coefficient analysis, and coefficient of determination analysis. The results of the study show that the indicators used for each of these variables show that the description of the marketing mix variable is in the very good category. The description of the purchase decision variable is in the very good category. Based on the test of the determinant coefficient, the magnitude of the effect is very strong or very high between the two variables.